Exporting norm interpretations from the Global South: Explaining India's reasons for contesting and reshaping international climate norms - Chris Höhne (Earth System Governance)
Recent scholarship highlights Global South countries not only as norm-takers or localizers but also as norm-makers. Contributing to this shift, I conceptualize why these countries contest and lobby for alternative norm interpretations in international negotiations. Applying this lens to climate politics, I use triangulated data (incl. expert interviews) to identify domestic factors that explain the Indian government's behavior. By exporting domestic norm interpretations that merged with other norm interpretations from Global North and South countries, the Indian delegation successfully reshaped two international climate norms at the 2007 Bali Conference that target developing countries' mitigation efforts and climate action in forests. This increased the resonance of these two norms with the Indian government's domestic norms, political economy beliefs, international funding desire and collective identity needs. This research provides insights into the complex dynamics of international norm negotiations between proposers and counter-proposers in the context of the rise of the Global South.